Activated impurity states in the incommensurate phase of ferroelectric semiconductor TlInS2 - Seyidov, MirHasan Yu.; Suleymanov, Rauf A.; Salehli, Ferid (Amer Inst Physics, 2010)
The effect of annealing within the incommensurate phase on the dielectric function epsilon of the TlInS2 single crystals has been investigated. It is shown that the effect of annealing is very close to the effect of doping by electrically active impurity La. The inference is made that the correlation between observed effects in annealed and doped crystals is conditioned by the internal electric fields induced by the activation (polarization) of native defects during the annealing procedure. The investigations of the Second harmonic generation in undoped TlInS2 crystal and the pyrocurrent in TlInS2 : La confirms the proposed model. (C) 2010 American Institute of Physics. [doi:10.1063/1.3466764]
Keywords: Dielectric-Properties; Transitions; Crystals; Tlgase2